Characterization of the DNA in DROSOPHILA MELANOGASTER - Travaglini, E. C. (1972)
DNA has been quantitatively extracted from Drosophila melanogaster at various stages of embryonic development and analyzed by isopycnic centrifugation in CsCl and by fractionation on methylated albumin columns. The DNA is composed of three main classes of DNA, as defined by their buoyant density, ρ, in CsCl: a bulk DNA, ρ = 1.699 g cm(-3), and two satellite DNAs, ρ = 1.685 g cm(-3) and ρ = 1.669 g cm(-3). These three types of DNA persist throughout the development of the insect. In the unfertilized egg, 80% of the total DNA consists of the satellite DNAs; this amount decreases to 18% during the first three hours after fertilization and then remains constant through embryogenesis. There is a concomitant increase of the satellite DNA's with the bulk DNA after blastoderm formation.